Ritual y estructura social en Maragatería (Estudios humanísticos. Geografía, historia y arte, 1988)
The traditional male inmigration in an area of León, has brought with it certain characteristics pertaining to the way of life among its population. Because of the absence of the male population, women have tended to assume predomina te roles in agriculture and livestock raising, while men have primarily dedicated themselves to commercial activities.In this paper, two festivals are anlyzed thet take place in a certain community of the district of "Maragatería".These two festivals express, in ritual form and in an exemplary complementary fashion, fundamental aspects of the district's social structure.